Pembentukan UMKM Varisko sebagai Pemberdayaan dan Solusi Ekonomi Masyarakat Cumedak Jember - Alfina Wildatul Fitriyah; Faizatur Robiatil Adawiyah; Saini Saini (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Varisko micro business as an empowerment effort and economic solution for the community of Cumedak Village, Jember. Cumedak Village faces significant economic challenges, marked by an unemployment rate of 12% and poverty rate of 18%, as well as the majority of the population's dependence on the agricultural sector with unstable incomes. This study aims to analyze and develop the formation of Micro, Small, and Medium Enterprises (UMKM). The study employs a descriptive qualitative approach with a case study design. Data collection was conducted through participatory field observations, in-depth interviews with residents and MSME actors, as well as documentation of activities. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. The results of the assistance showed a significant increase in the technical capabilities of production, product quality, and operational efficiency of Varisko MSMEs. Training in business management and digital marketing strategies succeeded in increasing sales by 35% during the assistance period. In addition, this program had a positive social impact by increasing the participation, confidence, and motivation of MSME members, as well as strengthening social networks and solidarity among residents. Despite challenges such as the incompatibility of the proponents' fields of study, community controversy regarding involvement and sustainability, as well as low initial interest and lack of community understanding, solutions in the form of persuasive education,  practical technical training, flexible scheduling, and assistance with access to capital and legality were successfully implemented. In conclusion, the establishment of Varisko SMEs has proven effective as a means of empowerment and a sustainable economic solution for the community of Cumedak Village, not only increasing income but also strengthening social aspects and self-reliance.